The Curricularization of University Extension: The Student Participation from the Experience of Health Promotion and Local Entrepreneurship Project in Puriscal, Costa Rica - Gamboa-Conejo, Rita (2016)
The National University was created in 1973 under a humanist, democratic and inclusive perspective. This house of studies emerged as a higher education option to serve as an alternative offered to the rural and urban social sectors whose access to university education was limited at that time; in addition, its creation responded to the concerns of the new generations of counting with an accessible center of higher studies and academic excellence in the country. Since its creation, the National University adopted the integration of three fundamental pillars for the fulfillment of its raison d’être: teaching, research and extension. This presentation makes emphasis on the university extension as an axis that integrates processes of creation and development of capabilities of its social, institutional and local actors, and social transformation to a higher quality of life for the communities (A, 2009). Over the years, the role of university extension has been weakened, despite the fact that it is one of the components of the university work that permanently interacts with communities and social groups. However, the integration of that function with teaching and an effective feedback of the curriculum profiles through its implementation is not the common characteristic in the academic work. Consequently, this situation has led to the weakening of the extension over the years and, little by little, this function has been relegated and, as popularly said, it is the academic Cinderella maintained thanks to the motivation of some teachers, who make greater efforts despite the inappropriate conditions they face. The School of Planning and Social Promotion represents a particular case of the curricularization of extension in its curriculum. This specifically happens in the third year of career, when doing an annual internship of 12 credits (6 credits per semester). According to the Internship Program (2014), its goal is “to allow a first approach to the communal, institutional and organizational reality, taking into account the institutional framework in which the different social actors (students, teachers, organizations, enterprises, institutions) live a learning process through the participative construction of actions and potential projects for economic, social and environmental development”. This student practice aims to facilitate the intrinsical union of the theory-practice in the Economic and Social Planning career. The project, funded by the National Council of Rectors, is called “Equity, and Citizen Participation: Health Promotion and local entrepreneurship in Puriscal (EPASOP)”. Its experience serves as a point of departure to support the relevance of the university extension work and student participation. From this approach, it is shown the implications of a curriculum that integrates the extension to the academic training and that generates a student active participation, where the pedagogical process is strengthened with a vision or pedagogical and humanist richness. As added value, this exercise presents the academic, social and individual impact of the curricularization of extension in a university career.